Oral Metronomic Chemotherapy in Nasopharyngeal Carcinoma with Radiotherapy Interruptions: A Lesson Learned from the Lockdown Due to COVID-19 - Zhou, Yuan; Zhou, Rui; Yu, Yi-Feng; Huang, Zheng-Jie; Wu, San-Gang (Recent Patents on Anti-Cancer Drug Discovery, 2025)
<span class=
Keywords: radiotherapy interruptions